Faktor Yang Berhubungan Dengan Kejadian Obesitas Pada Anak Sekolah Di Sdn 002 Sapat Kecamatan Kuala Indragiri Riau Tahun 2021 - Nadiya Zia Nurhaliza; Zuraidah Nasution; Ramadhani Syafitri Nasution (Jurnal Kesehatan dan Fisioterapi, 2023)
The process of growth and development of every child requires balanced nutrition. Balanced nutritional elements include carbohydrates, fats, proteins, vitamins, water and minerals in the right proportions. Parents often think that a healthy child is a fat (obese) child. This study aims to find out what factors are related to the incidence of obesity in school children at SDN 002 Sapat, Kuala Indragiri District, Riau in 2021. The research method is an analytic survey research using a cross-sectional approach. The population in this study were all students in grades IV, V, and VI at SDN 002 Sapat, Kuala Indragiri District, totaling 79 people. Sampling in this study used a total sampling technique and the analysis used included univariate, bivariate, and multivariate analysis with multiple logistic regression. The results show that there are factors associated with the incidence of obesity in school children, namely maternal education (p=0.000), genetics (0.010), and diet (p=0.000), while factors that are not related are physical activity (p=0.086) and family income. (0.383). Conclusion: There is a relationship between a mother's education, genetics, and diet with the incidence of obesity in school children at SDN 002 Sapat, Kuala Indragiri District, Riau. The suggestion in this study is for teachers in schools to increase student activity to be more active, for example by inviting students to exercise in the morning and be active in sports lessons.Keywords: Mother's education, physical activity, genetics, family income, diet and obesity.